Two-step sublevel open stoping with backfilling technology and application for low-grade orebody - Xu, Pei-Liang; Wang, Jun; Hou, Ke-Peng; Qiao, Deng-Pan; Yang, Tian-yu (Frontiers in Earth Science, 2025)
IntroductionThe Dahongshan copper mine presents complex mining challenges due to its gently dipping, thin to medium thickness copper and iron orebodies occurring in parallel interbedded layers with moderately stable surrounding rock.MethodsTo address these challenges and optimize mining operations, a “copper and iron co-mining” model was proposed. This model was implemented using a two-step sublevel open stoping with backfilling mining technology. Key supporting technologies developed include: an economic cut-off grade model for co-mining; a strength model of cemented backfill coupled with layered precision backfilling technology; a fundamental theory of continuous high-concentration steady-state sand discharge from vertical silos leading to multi-silo parallel continuous high-concentration steady-state sand discharge technology; and a strength and structural design model for retaining walls enabling rapid construction using shotcrete retaining walls.ResultsThis integrated technology achieves safe, efficient, and economical mining of the Dahongshan copper mine’s gently dipping, multi-layered, thin to medium thickness, low-grade orebodies. It effectively extends the mine’s service life and demonstrates significant application results, economic benefits, and social benefits.DiscussionThe research results from the Dahongshan copper mine are of great significance for advancing mining theory and possess high application and promotion value for similar mining operations facing comparable challenges.